2010
DOI: 10.1063/1.3336747
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption and photoemission spectroscopy of zinc protoporphyrin adsorbed on rutile TiO2(110) prepared by in situ electrospray deposition

Abstract: Zinc-protoporphyrin, adsorbed on the rutile TiO(2)(110) surface, has been studied using photoemission spectroscopy and near-edge absorption fine structure spectroscopy to deduce the nature of the molecule-surface bonding and the chemical environment of the central metal atom. To overcome the difficulties associated with sublimation of the porphyrin molecules, samples were prepared in situ using ultrahigh vacuum electrospray deposition, a technique which facilitates the deposition of nonvolatile and fragile mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 35 publications
11
81
0
Order By: Relevance
“…In potassium doped ZnPc films it was shown that although the HOMO/LUMO shifted by 0.6 eV with respect to the Fermi level, Zn3d remained at the same position. In our case, the different shifts in Zn3d, C1s and N1s are a combined result of 1) the loss of electrons in the molecule mainly affects the inner ring of the molecule 28 put zinc protoporphyrin on TiO 2 , which has a similar molecular structure as ZnPc, and observed a removal of the zinc atom from the central porphyrin ring. This resulted in a Zn2p shift to lower binding energy compared the thick film, indicating a more neutral zinc atom on the surface.…”
Section: Photoelectron Spectroscopymentioning
confidence: 96%
“…In potassium doped ZnPc films it was shown that although the HOMO/LUMO shifted by 0.6 eV with respect to the Fermi level, Zn3d remained at the same position. In our case, the different shifts in Zn3d, C1s and N1s are a combined result of 1) the loss of electrons in the molecule mainly affects the inner ring of the molecule 28 put zinc protoporphyrin on TiO 2 , which has a similar molecular structure as ZnPc, and observed a removal of the zinc atom from the central porphyrin ring. This resulted in a Zn2p shift to lower binding energy compared the thick film, indicating a more neutral zinc atom on the surface.…”
Section: Photoelectron Spectroscopymentioning
confidence: 96%
“…9,13 The average orientation of adsorbed molecules relative to the surface could be derived from combined near-edge x-ray absorption fine structure spectroscopy (NEXAFS) and photoelectron spectroscopy (PES). [14][15][16] However, the irregular mesoporous titania surface prevents averaging techniques from capturing 4 local molecular details. Scanning probe techniques can in principle overcome this difficulty and provide direct, local information about the adsorbed layer.…”
Section: Introductionmentioning
confidence: 99%
“…18 This electronic effect on the surface Ti atoms is further enhanced upon the formation of a (1 Â 2) surface reconstruction, induced by high-temperature annealing. 19 Very recently, the strong structural anisotropy of the TiO 2 -(110) surface has been tentatively exploited as a template to drive the oriented growth of planar organic molecules, such as phthalocyanines, [20][21][22] porphyrins, 23 and perylene derivatives. [24][25][26] When these molecules adsorb flat onto the substrate, the intralayer lateral transport is inhibited, but a much faster charge transfer to the substrate has been reported.…”
Section: Introductionmentioning
confidence: 99%